EFEK PERIMBANGAN PUPUK ORGANIK DAN PUPUK ANORGANIK TERHADAP SIFAT KIMIA TANAH ANDISOL TAWANGMANGU DAN HASIL TANAMAN WORTEL (Daucus carota L.) - Slamet Minardi; Joko Winarno; Abror Hanif Nur Abdillah (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2009)
Title : Effects of Balance Organic and Inorganic Fertilizer on the Andisols Soil Chemistry at Tawangmangu to Yield of Carrot (Daucus carota L.). This research was carried out from August 2008 to February 2009. The purpose of this research were to know the effect of litter quality of Gliricidia maculata and Salacca edulis to inhibition of nitrification and efficiency N benefit in Alfisols. This research were conducted in Blumbang, Sub district Tawangmangu, Karanganyar Regency. The aim of this research to know the effect of balance organic fertilizer and inorganic fertilizer to Andisols soil chemistry at Tawangmangu. This research was experimental research which is used RCBD (Randomized Complete Block Design) with single factor: trial pattern P1 (0% organic fertilizer + 0% inorganic fertilizer), P2 (50% inorganic fertilizer), P3 (100% inorganic fertilizer), P4 (50% organic fertilizer), P5 (50% organic fertilizer + 50% inorganic fertilizer), P6 (50% organic fertilizer + 100% inorganic fertilizer), P7 (100% organic fertilizer), P8 (100% organic fertilizer + 50% inorganic fertilizer), P9 (100% organic fertilizer + 100% inorganic fertilizer). Statistical analysis to test about treatment influence used F-test and Kruskal-wallis test, for comparing inter-treatment used Duncan Multiple Range Test (DMRT) and Mood Median, for finding out of the relation inter-variable it is used correlation test. The result of the research shows that the balance of organic fertilizer and inorganic fertilizer give significant effect to increase total N soil, available N soil, Cation Exchange Capacity (CEC), and pH H2O, but it has not significant effect to total P soil, available P soil, total K soil, available K soil, pH NaF, Base Saturation (BS), and Organic Matter. The Highest total N soil was 0,56% with increased percentage 38.8% from control and CEC was 28.08 me%, increased 4.87 me% from control in balanced 100% organic fertilizer and 100% inorganic fertilizer, affected to yield of carrot was 138.5 g increased 27.3 g (24.5%) from control. Keywords: Organic fertilizer, Inorganic Fertilizer, Andisols, Soil Chemistry, Carrot